Handbook of law for police officers - "Narasimhan, C. V." (New Delhi, 1991)
Rule of law is fundamental to democracy. Law provides the framework, not only for the maintenance of public order and security of life and property, but also for giving shape to important social changes in keeping whti the directive principles of the constitution.
Keywords: Law - Handbook